Selection of occupation therapy students for the BSc OT course at the University of the Witwatersrand - De Witt, Patricia Ann (My University, 2014)
The purpose of this study was to determine if any of the criteria used for admission to the BSc Occupational Therapy (OT) Course offered by the University of the Witwatersrand, could differentiate between those students who passed and failed. 236 students admitted to the BSc OT course between 1982 and 1987 were divided into 4 groups: those who passed all courses on first attempt; those who failed one or more courses on first attempt but had completed or would complete the course; those who failed one or more courses on first attempt and left; those who passed all courses and left. An analysis of variance was then carried out on each of the 4 groups for the following selection variables.